General digital competences of beginning trainees in commercial vocational education and training - Findeisen, Stefanie [Verfasser]; Wild, Steffen [Verfasser] (My University, 2022)
“Against the background of digital transformation processes that are currently changing the world of work, this paper examines general digital competences of beginning trainees in commercial vocational education and training (VET) programs. We are particularly interested in factors influencing digital competence profiles. From survey data including N = 480 trainees in one federal state in Germany, we were able to identify three different competence profiles (based on the trainees’ self-assessment of their general digital competence). Initial descriptive analysis reveals differences between competence profiles of different training professions (industrial clerks and retail salespersons reach higher competence levels than salespersons). However, regression results indicate that these differences can be explained by differences in school leaving certificates. Contrary to prior empirical evidence, we find no significant effect of trainees’ gender. Finally, the frequency of certain private digital activities (e.g. using office programs, conducting internet searches) affects digital competence profiles. Implications for both VET programs and further research are discussed.“ (authors’ abstract; BIBB-Doku)
Keywords: P 2.3 Auszubildende; Baden-Württemberg; 370; Kaufmännische Ausbildung; Auszubildender; Digitalkompetenz; Kompetenzprofil; Kaufmännischer Beruf; Baden-Württemberg